Influence of the saturation-suction relationship in the formulation of non-saturated soils consolidation models - Di Rado, Hector Ariel (2009)
The main scope of this paper is to present a fully coupled numerical model for isothermal soil consolidation analysis based on a combination of different stress states. Being originally a non symmetric problem, it may be straightforward reduced to a symmetric one, and general guidelines for the conditions in which this reduction may be carried out, are addressed. Non linear saturation-suction and permeabilitysuction functions were incorporated into a Galerkin approach of the non-saturated soil consolidation problem, which was solved using the finite element method. In order to validate the model, various examples, for which previous solutions are known, were solved. The use of either a strongly non linear and non symmetric formulation or a simple symmetric formulation with accurate prediction in deformation and pore-pressures is extremely dependent on the soil characteristic curves and their derivatives and this aspect is taken into account in the present mathematical approach. The emergent coupling effects may be easily uncoupled in the computer model by merely recasting some coefficients of the discrete equation system.